EVALUATION OF CERTAIN BLACKGRAM VARIETIES FOR RESISTANCE TO PULSE BRUCHID, Callosobruchus maculatus (F.) - S. V. S. GOPALA SWAMY (The Journal of Research ANGRAU, 2016)
A laboratory experiment was conducted to know the relative susceptibility of blackgram varieties to pulse beetle at Post Harvest Technology Centre, Bapatla during 2014-15. The Trombay blackgram varieties- TU 80 and TU 68 were found resistant to the pulse bruchid as the number of eggs, 2.67 and 3.0/ 100 seeds, respectively and adults, 1.33 and 4.33 emerged were significantly less compared to the other varieties. The variety LBG 752 recorded higher number of eggs, 25.67 /100 seeds and 189.0 adults emerged in 80 days. Grain damage was 0.33 and 1.0% and percent weight loss was 0.04 and 0.1, which were also significantly less in TU 80 and TU 68 when compared to LBG 752 (99.33% and 39.53%).The developmental periods of pulse beetle on TU 80 and TU 68 were also longer compared to LBG 752 and TU 72 indicating the presence of some antibiotic constituents.